Systemic lupus erythematosus, following prodromal idiopathic thrombocytopenic purpura, presenting with skin lesions resembling malignant atrophic papulosis. (10th July 2017) - Wallace, M. P.; Thomas, J. M.; Meligonis, G.; Ha, T.
Summary: Systemic lupus erythematosus (SLE) is an autoimmune disease. Its incidence in the UK is approximately 1 per 10 000. Cutaneous involvement, encompassing acute, subacute and chronic disease, occurs in over two‐thirds of cases, and can often be the first clue to diagnosis. We describe a highly unusual case of SLE occurring after prodromal idiopathic thrombocytopenic purpura (ITP) and presenting with skin lesions more typical of malignant atrophic papulosis, a rare and often fatal vasculopathy. Such a combination of rare features emphasizes the potential for complexity in this multisystem disease.